Short Communication Spectrophotometric Determination of Cetirizine Dihydrochloride in Pure and Pharmaceutical Formulations: Short Communication: Determination of Cetirizine Dihydrochloride - Mumtaz, Amina; Kazi, Asrar Ahmad; Aman, Tehseen; Zehra, Jesmine (Biological Sciences - PJSIR, 2010)
A rapid, simple and sensitive spectrophotometric method has been developed for determination of antihistamine (cetirizine dihydrochloride) in pure and pharmaceutical formulations, based on the charge transfer complexation between cetirizine dihydrochloride as n-electron donor with dichloronitrobenzene as p-acceptor in basic medium. The resulting yellowish orange coloured complex had absorption maxima at 410 nm. Beer’s law is obeyed in the concentration range I0 mg to 250 mg/mL. Molar absorptivity is 0.4805´104/mol/cm and relative standard deviation is 0.95%.